Broad diversity of conjugative plasmids in integron-carrying bacteria from wastewater environments - Moura, Alexandra (2019)
In this study we assessed the occurrence, diversity and conjugative potential of plasmids in integron-carrying Aeromonas and Enterobacteriaceae from wastewaters. Sixty-six strains were included as donors in mating assays using rifampicin-resistant Escherichia coli and Pseudomonas putida recipient strains. The diversity of plasmids from donors and transconjugants (resistant to tetracycline or streptomycin) was evaluated by restriction analysis and replicon typing targeting 19 incompatibility groups. Restriction patterns revealed a diverse plasmid pool present in these strains. Plasmids were assigned to FrepB (Aeromonas salmonicida, Aeromonas veronii, Aeromonas sp., E. coli, Enterobacter sp.), FIC (A. salmonicida, Aeromonas sp.), FIA (Shigella sp.), I1 (A. veronii, Aeromonas sp., E. coli), HI1 (E. coli) and U (Aeromonas media) replicons. Nevertheless, 50% of the plasmids could not be assigned to any replicon type. Among integron-positive transconjugants, FrepB, I1 and HI1 replicons were detected. Results showed that wastewaters enclose a rich plasmid pool associated with integron-carrying bacteria, capable of conjugating to different bacterial hosts. Moreover, replicons detected in this study in Aeromonas strains expand our current knowledge of plasmid diversity in this genus.